2014
DOI: 10.1177/1470320314547403
|View full text |Cite
|
Sign up to set email alerts
|

The insertion and deletion (I28005D) polymorphism of the angiotensin I converting enzyme gene is a risk factor for osteoarthritis in an Asian Indian population

Abstract: Introduction: Angiotensin I converting enzyme (ACE) insertion and deletion (I/D) polymorphism has been implicated in the pathogenesis of osteoarthritis (OA). In recent years, numerous genetic factors have been identified and implicated in OA. In this Asian Indian population-based study, we aimed to evaluate the relationship between ACE (I28005D) gene polymorphism and primary OA. We performed a case-control association study to identify and explore the correlation between clinically, radiologically diagnosed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In reports by Bayram et al (2011) and Inanir et al (2013), the DD genotype of the ACE gene I/D polymorphism was associated with knee OA in a Turkish study population [ 38 , 39 ]. Poornima et al (2015) observed the same phenomenon in an Asian Indian population [ 40 ]. In contrast with our hypothesis, the above three studies considered that D allele carriers had the greater risk of OA.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In reports by Bayram et al (2011) and Inanir et al (2013), the DD genotype of the ACE gene I/D polymorphism was associated with knee OA in a Turkish study population [ 38 , 39 ]. Poornima et al (2015) observed the same phenomenon in an Asian Indian population [ 40 ]. In contrast with our hypothesis, the above three studies considered that D allele carriers had the greater risk of OA.…”
Section: Introductionmentioning
confidence: 76%
“…Of the remaining six papers, one paper did not have sufficiently detailed data for the analysis. Accordingly, five studies were included in our meta-analysis [ 36 40 ], and detailed data are presented in Table 3 . Our meta-analysis therefore comprised three Asian studies and three Arab studies, including our case–control study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations